Transient paraplegia due to subarachnoid haemorrhage following spinal anaesthesia. Issue 1 (5th June 2020) - Olivei, M. C.; Tamanti, P.; Giachetti, A.; Nespoli, P.; Berta, G.; Caironi, P.
Summary: Spinal subarachnoid haemorrhage is a rare complication of spinal anaesthesia, especially following atraumatic lumbar puncture and in the absence of coagulopathies. The initial presentation of spinal subarachnoid haemorrhage is variable and paraplegia with full recovery within a few hours is rare. Bleeding can extend into the intracranial subarachnoid space, but there are only a few reports of symptomatic intracranial and spinal subarachnoid haemorrhage after spinal anaesthesia. We report co‐existing spinal subarachnoid haemorrhage and intracranial subarachnoid haemorrhage after atraumatic spinal anaesthesia in a 69‐year‐old woman without a coagulopathy. The day after surgery she developed flaccid paraplegia that spontaneously resolved in a few hours. Magnetic resonance imaging demonstrated subarachnoid high signal intensity from T11–S2, consistent with spinal subarachnoid haemorrhage. On the same day the patient complained of severe headache which was later followed by diplopia. Neurological imaging studies revealed diffuse distribution of blood in the subarachnoid space but no intracranial vascular malformations. At the time of diagnosis spontaneous recovery of spinal symptoms had already begun and the clinical manifestations eventually resolved with conservative management. The possibility of an intracranial haemorrhage should always be considered when spinal subarachnoid haemorrhage is identified, even in cases of uncomplicated spinal anaesthesia in patients with no known risk factors for spinal haemorrhage.